E-government in Hungarian agriculture: a case study - Csótó, Mihály; Szénás, Szilárd (Acta Agraria Kaposváriensis, 2010)
The past decade brought major changes in the development of ICT tools and systems as well in the area of applications and services based on them. This development opened up new opportunities for the agro economy and in many areas it provided access to tools that are now regarded as indispensable. Such progress is of especial importance for Hungarian agriculture, which has long been facing the problem of an inadequate ICT provision level. This problem is aggravated by the fact that – especially after Hungary’s accession to the EU – the administrative costs of farmers have been extremely high. In accordance with international trends and in order to remedy already existing problems the Agricultural and Rural Development Agency and the Central Agricultural Office introduced electronically filled-in and submitted claim forms in 2007 with the objective of simplifying procedures related to the payment of agricultural subsidies, and after this service was gradually expanded over the following two years it eventually fully replaced the off-line method of submission. The authors wish to provide an overview of this process, focusing on the most important changes introduced in the past three years as well as on the advantages and disadvantages experienced on both the administrative and the farmer/user side. This is the first time the authors - based on their earlier work - have tried to give a comprehensive analysis of both "target groups" (front and back office) of the e-application system.